2020
DOI: 10.3390/nu12010190
|View full text |Cite
|
Sign up to set email alerts
|

Next Steps for Interventions Targeting Adolescent Dietary Behaviour

Abstract: Adolescents in many countries consume poor quality diets that include high intakes of sugary drinks and fast food and low intakes of vegetables. The aims of this Special Issue on adolescent dietary behaviour were to identify methods and approaches for successful interventions to improve diet quality in this age group and identify at risk subgroups that need particular attention. In total, 11 manuscripts were published in this Special Issue—three qualitative studies which included a systematic review, five cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In contrast, systems-like approaches that consider issues with a complex breadth of interconnected causes, interactions, and effects have gained relevance in recent years and have helped us to better understand critical food-related issues, such as obesity or unhealthy eating [ 27 , 28 , 29 ]. Scholars are also increasingly recognizing the importance of such comprehensive approaches for accurately assessing the (multiple) effects of a given policy and calling for their systematic use for the promotion and the evaluation of food policies [ 30 , 31 , 32 , 33 ]. Our work contributes to the development of such approaches by proposing a multilevel framework of food policy acceptability.…”
Section: A Model Of Food Policy Acceptabilitymentioning
confidence: 99%
“…In contrast, systems-like approaches that consider issues with a complex breadth of interconnected causes, interactions, and effects have gained relevance in recent years and have helped us to better understand critical food-related issues, such as obesity or unhealthy eating [ 27 , 28 , 29 ]. Scholars are also increasingly recognizing the importance of such comprehensive approaches for accurately assessing the (multiple) effects of a given policy and calling for their systematic use for the promotion and the evaluation of food policies [ 30 , 31 , 32 , 33 ]. Our work contributes to the development of such approaches by proposing a multilevel framework of food policy acceptability.…”
Section: A Model Of Food Policy Acceptabilitymentioning
confidence: 99%
“…Peer-led, school-based nutrition initiatives have the potential to improve dietary attitudes, knowledge and self-efficacy (106) , and therefore, peer-led interventions in school are also receiving increasing attention as an effective means to promote improved dietary behaviours among adolescents. It has been suggested that when targeting adolescents' dietary behaviours, adolescent-led interventions may increase effectiveness as they may be more aware of this population's values (107) . Peer involvement has been reported as an important contributing factor to the success of school-based dietary interventions among adolescents and should be considered in future intervention design (19,39) .…”
Section: Peer-led Interventionsmentioning
confidence: 99%
“…Adolescents are aggressively targeted by food marketing messages (primarily for unhealthy foods) and susceptible to this messaging due to developmental vulnerabilities and peer-group influence [44] . Restaurant, food, nutritional supplements, and beverage advertising targeted to adolescents almost exclusively promotes energydense nutrient-poor products, especially fast food, sugary drinks, candy, and snacks [45,46] .…”
Section: Nutritionmentioning
confidence: 99%